Validation of a Method for Determining the Content of Elemental Impurities in the Radiopharmaceutical [18F]-PSMA-1007 by Inductively Coupled Plasma Mass Spectrometry - V. M. Shchukin; Yu. N. Shvetsova; A. A. Erina; N. E. Kuz'mina (Regulatory Research and Medicine Evaluation, 2026)
INTRODUCTION. According to pharmacopoeial requirements, during the development and validation of the manufacturing process for radiopharmaceuticals, it is necessary to determine the content of impurities such as Pb, As, and Fe, as well as other elements that contribute most to the contamination of the drug product (for [ 18 F]-PSMA-1007, these elements are Al, Zn, Cu, and Li). Previously, we developed a method for quantifying elemental impurities in [ 18 F]-fluorodeoxyglucose using inductively coupled plasma mass spectrometry. The current study aims to assess its applicability to [18F]-PSMA-1007. AIM. Validation of the method for determining the content of Al, As, Cu, Zn, Fe, Pb and Li in the radiopharmaceutical [18F]-PSMA-1007 by inductively coupled plasma mass spectrometry. MATERIALS AND METHODS. The tests were carried out on a sample of the radiopharmaceutical [ 18 F]-PSMA-1007 with minimal content of the target impurities, to which varying amounts of standard solutions of the determined elements were added. The content of elements was determined using an Agilent 7900 mass spectrometer; the signal intensities of isotopes (amu) 7Li, 27Al, 57Fe, 63Cu, 66Zn, 75As, and 208Pb were recorded. RESULTS. It was established that the method for determination of elemental impurities in the radiopharmaceutical [ 18 F]-PSMA-1007 meets the validation requirements specified in the State Pharmacopoeia of the Russian Federation, 15th edition. The correlation coefficient of the linear dependence of signal on concentration for all determined elements is ≥0.99; the ratio of relative standard deviations at the minimum and maximum calibration levels is in the range of 0.5–2.0. The recovery of the method is characterized by acceptable accuracy (80–120%) for all determined elements. The relative standard deviation for all elements is ≤20% (repeatability) and ≤25% (intermediate precision). The actual values of the Fisher and Student test criteria are significantly below the critical values. The specificity of the method was confirmed, which allows unambiguous determination of each element in the presence of other elemental impurities and components. CONCLUSIONS. The analytical method for determining elemental impurities by mass spectrometry in [ 18 F]-fluorodeoxyglucose is applicable to the radiopharmaceutical [ 18 F]-PSMA-1007. The method can be used by manufacturers of this radiopharmaceutical both for validation of their manufacturing process and, if necessary, for internal quality control of their products.